Հայրենիքի և հոգու ընտրության շարունակական խնդիրները Վ. Շուշանյանի «Սիրո և արկածի տղաքը» վեպում - Նելլի Թադևոսյան (ՀՀ ԳԱԱ հրատ.)
В статье анализируются основные положения романа прозаика армянской диаспоры Вазгена Шушаняна “Парни любви и приключений’’.Первой проблемой является выбор родины. Герои романа не смиряются с отчужденной Арменией и выбирают Духовную, Культурную родину. Следующая проблема касается восприятия любви, в которой автор- герой придает большее значение духовному единению, чем физическому. Перед роковым выбором между родиной и любовью герой-Шушанян остается верным своему внутреннему “Я’’.This article studies the issues in Shushanyan’s novel, “The Boys Of Love And Adventure”. The first concerns the choice of Homeland. The heroes of the novel do not cope with Armenia from which they feel alienated. They rather prefer a Spiritual and Cultural Homeland. The other relates to the perception of love, where the author-hero gives more importance to the unification of souls than to the corporeal one. Faced with two major choices between Homeland and love, the Shushanyanhero eventually remains faithful to his inner “self”.
Keywords: Language and Literature